Bacillus spp. on the growth and yield of Capsicum chinense Jacq. - Mejía-Bautista, Miguel Ángel; Cristóbal-Alejo, Jairo; Pacheco-Aguilar, Juan Ramiro; Reyes-Ramírez, Arturo (Revista Mexicana de Ciencias Agrícolas, 2022)
Plant growth-promoting rhizobacteria are an alternative to improve the production and yield of horticultural crops such as habanero pepper in Yucatan. Eleven strains of the genus Bacillus, characterized by their properties related to the promotion of plant growth, were evaluated, finding the production of indole acetic acid from 0.046 to 5.45 μg ml-1, phosphate solubilization indices from 2.1 to 2.76 mm and from 13.01 to 55.82 mg L-1 of soluble phosphorus and ACC deaminase activity. Of which four strains with the best characteristics were selected for their properties with the promotion of plant growth, using as a model the habanero pepper, in which it was obtained that the strain of Bacillus subtilis CBMT51 promoted the growth of habanero pepper seedlings, improving in the number of leaves, leaf area and biomass of the seedlings by 37.1, 30% and 34.6%, respectively. In greenhouse tests with the same strain, an increase in the number of fruits and crop yield of 79.5% and 58.8%, respectively, was observed, in relation to the control. With B. subtilis CBMT2 being the strain that improved some growth variables such as final height (56%), number of shoots (92%) and total dry biomass (86%) with respect to the control. In conclusion, the results of this work show the potential of the strain of B. subtilis CBMT51 to be used as a biofertilizer in the production of habanero pepper.